Contemporary perspectives on language policy and literacy instruction in early childhood education - Saracho, Olivia N.; Spodek, Bernard (Emerald Publishing Limited : Information Age Publishing, 2004)
In this anthology, Saracho (curriculum and instruction, University of Maryland) and Spodek (early childhood education, University of Illinois) present work reviewing the current state of knowledge on the education of students who are not fully proficient in English. The editors attempt to move beyond the narrow focus of language instruction that has dominated education and policy discussions to examine individual, social, and instructional factors that affect English language learners.
Keywords: Language arts (Early childhood) -- Social aspects -- United States.; Language policy -- United States.; Limited English proficient students -- United States.; Education -- Schools -- Levels -- Early Childhood (incl. Preschool & Kindergarten); Early childhood care and education.; Pre-school and kindergarten.; elektronické knihy; electronic books